Observing and Measuring Government Openness. A conceptual discussion and application to Mexico (2018)
Open government has become a goal for countries all over the world, but it remains an elusive concept. Despite innovative methodologies to assess open government policies, action plans, and interventions in different countries, scholarly research and practical decisions are hindered by the lack of a precise concept and an operationalization. In this paper, we make two contributions to this discussion. First, we argue that the discussions about open government would benefit from taking the grammatical structure of the concept seriously (open is an adjective, government a noun). Second, we propose that, in order to be conceptually and practically useful, open government should be observable. We present the methodology, application and results of an effort to observe and measure open government in Mexico, based on a study of 908 government offices in terms of transparency and participation.